Antibacterial activity of promising nanostructured cesium oxide - Wedam Alghazzawi (Discover Nano)
Abstract As bacterial strains become increasingly resistant to antibiotics, many researchers are seeking novel, effective, and inexpensive antibiotics. Some nanomaterials have been suggested as potential candidates for use as novel antibacterial agents. In this study, cesium oxide nanoparticles were synthesized and preliminarily investigated for their ability to inhibit the growth of bacteria. Although there are few studies on the applications of cesium oxide, it is possible that this oxide could have a substantial impact on biological activities. Cesium oxide nanoparticles were synthesized via fast calcination at 500 °C for 3 h. The composition and morphology of the prepared samples were characterized via X-ray diffraction, Fourier transform infrared spectroscopy, energy dispersive X-ray spectroscopy, and scanning electron microscope analysis, which verified the synthesis of cesium oxide nanoparticles. Agar well diffusion and minimum inhibitory concentration assays were used to study the antibacterial activity of cesium oxide nanoparticles against gram-positive and gram-negative bacteria. The experimental results provide preliminary support for developing cesium oxide nanostructures as antibacterial agents against a wide range of infections and diseases caused by bacteria. Graphical abstract